Does changing the configuration of a motor racing circuit make it safer?. Issue 3 (23rd February 2005) - Leonard, L; Lim, A; Chesser, T J S; Norton, S A; Nolan, J P
Abstract : Objectives: To assess the pattern of injuries presenting to a racing circuit medical centre in two three-year periods before and after two chicanes were built into the track. Methods: Medical centre records were used to identify all patients assessed during the two time periods. Those referred to hospital were categorised by injury severity into three groups. Results: The proportions of those attending the medical centre that were referred and admitted to hospital were the same in both periods (12–13% and 3% respectively). During the two study periods, the risk of a severe injury for a car driver decreased from 0.1% to 0.03% (p<0.05). For a motorcyclist, similar values were 0% and 0.2% (not significant). Conclusions: Chicanes have improved the safety of the racing circuit for car drivers, reducing the risk of injury.